Cytoplasmic Polyadenylation Element-Binding Protein 1 Post-transcriptionally Regulates Fragile X Mental Retardation 1 Expression Through 3′ Untranslated Region in Central Nervous System Neurons - Oe, Souichi; Hayashi, Shinichi; Tanaka, Susumu; Koike, Taro; Hirahara, Yukie; Seki-Omura, Ryohei; Kakizaki, Rio; Sakamoto, Sumika; Nakano, Yosuke; Noda, Yasuko; Yamada, Hisao; Kitada, Masaaki (Frontiers in Cellular Neuroscience, 2022)
Fragile X syndrome (FXS) is an inherited intellectual disability caused by a deficiency in Fragile X mental retardation 1 (Fmr1) gene expression. Recent studies have proposed the importance of cytoplasmic polyadenylation element-binding protein 1 (CPEB1) in FXS pathology; however, the molecular interaction between Fmr1 mRNA and CPEB1 has not been fully investigated. Here, we revealed that CPEB1 co-localized and interacted with Fmr1 mRNA in hippocampal neurons and HeLa cells. Furthermore, CPEB1 knockdown upregulated Fmr1 mRNA and protein levels and caused aberrant localization of Fragile X mental retardation protein in neurons. In an FXS cell model, CPEB1 knockdown upregulated the mRNA levels of several mitochondria-related genes and rescued the intracellular heat shock protein family A member 9 distribution. These findings suggest that CPEB1 post-transcriptionally regulated Fmr1 expression through the 3′ untranslated region, and that CPEB1 knockdown might affect mitochondrial function.